The Application of Human Resource Accounting on the Financial Performance of Insurance Companies in Indonesia 2022-2023 - Hamidah, Ine Suci; Widyarti, Maria Theresia Heni; Widiarto, Ardian (Ilomata International Journal of Social Science, 2025)
This study is conducted to analyze how insurance companies in Indonesia treat their human resources as assets and their effect on financial performance when the costs incurred are disclosed as assets in the financial statements presented. This research uses the secondary data of insurance companies listed in Indonesia stock exchange in 2022-2023 and uses an experimental method with a one group pretest-posttest design approach. The steps carried out are to simulate applying human resource accounting to the company's financial statements, to compare its financial performance by calculating, and statistically testing the financial ratios of return on assets, assets turnover and profit margin. The study found that insurance companies in Indonesia still apply conventional methods in their financial statements. applying human resource accounting increases the value of assets, equity, and total profit of the company. It also increases the value of return on assets and profit margin, but decreases the value of the company's asset turnover.